Understandıng Consumer Onlıne Purchase Intentıon Analyzed From Perceıved Rısk - humairoh humairoh; Mohammad Annas; Edwin Edwin (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The motive of this examination changed to determine the impact of financial risk, product risk, security risk, time risk, social risk, and psychological risk on shopping for interest in online purchasing for Roche Posay cosmetic products. The form of this study is explorative research. The sample on this examination was 150 respondents used a non-probability sampling method. The type of sampling used is judgmental sampling because the questionnaire is divided into samples that fall into the research category and the characteristics to be decided. Information evaluation used in this examination consists of a validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination test, and hypothesis testing. The information has been analyzed using the SPSS software version 26. The effects received were financial Risk, product risk, and psychological Risk, which negatively affected Roche Posay's online purchase intention. Social risk has an impact on online purchase intention but not negatively. Security risk and time danger do not negatively impact online purchase intention. The check at the model is 0.605, which means that the structured variable may be defined by using six independent variables of 60.5%.